Hierarchical Spiky Microstraws‐Integrated Microfluidic Device for Efficient Capture and In Situ Manipulation of Cancer Cells - He, Gen; Yang, Chengduan; Feng, Jianming; Wu, Jiangming; Zhou, Lingfei; Wen, Rui; Huang, Shuang; Wu, Qianni; Liu, Fanmao; Chen, Hui‐Jiuan; Hang, Tian; Xie, Xi (Advanced functional materials, 2019)
Techniques for capturing circulating tumor cells (CTCs) play an important role in cancer diagnosis. Recently, various 3D micro/nanostructures have been applied for effective CTC detection, yet in situ manipulation of the captured cancer cells on micro/nano‐structural substrates is rarely achieved. In this work, a hierarchical spiky microstraw array (HS‐MSA)‐integrated microfluidic device is demonstrated that possessed dual functions of cancer cell capture and in situ chemical manipulations of the captured cells. The 3D micro/nanostructure of HS‐MSA could capture cancer cells with high efficiency (≈84%) and strong specificity. Based on the HS‐MSA‐integrated microfluidic device, extracellular drug delivery to the captured cancer cells is achieved in situ with excellent spatial, dose, and temporal controls. In addition, a drug‐screening assay on the captured cancer cells is implemented to investigate the cell apoptosis behavior under the microstraw‐mediated delivery of staurosporine (STS). This microfluidic system not only presents tremendous potential for CTCs detection technology, but also opens up new opportunities for high‐throughput drug screening on cancer cells and understanding the cellular activity. Hierarchical spiky microstraw arrays (HS‐MSA) are designed that consist of a trunk hollow microtube structure with an inner fluidic conduit through the bottom substrate and numerous nanospikes. The HS‐MSA‐integrated microfluidic device is demonstrated to achieve efficient cancer cells capture and in situ chemical manipulations of the captured cells.